2013
DOI: 10.1002/eji.201243084
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury induces macrophage subsets in the brain

Abstract: Summary Traumatic brain injury (TBI) elicits innate inflammatory responses that can lead to secondary brain injury. To better understand the mechanisms involved in TBI-induced inflammation, we examined the nature of macrophages responding to TBI in mice. In this model, brain macrophages were increased >20-fold the day after injury and >77-fold four days after injury in the ipsilateral hemisphere compared with sham controls. TBI macrophage subsets were identified by using a reporter mouse strain (YARG) that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
144
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 55 publications
(77 reference statements)
14
144
0
5
Order By: Relevance
“…These data support other studies that evaluated macrophage and immune cell infiltration dynamics in TBI models. 30,31 Due to technical limitations when combining internalization staining protocols for M1-/M2-like markers with CD11b/CD45 cell surface markers, it was not possible to determine whether the infiltrating macrophages after were more M1-or M2-like polarized, but the peak in infiltration corresponded with high expression levels of both M1-and M2-like protein markers in this study.…”
Section: Fig 7 (Continued)mentioning
confidence: 87%
See 1 more Smart Citation
“…These data support other studies that evaluated macrophage and immune cell infiltration dynamics in TBI models. 30,31 Due to technical limitations when combining internalization staining protocols for M1-/M2-like markers with CD11b/CD45 cell surface markers, it was not possible to determine whether the infiltrating macrophages after were more M1-or M2-like polarized, but the peak in infiltration corresponded with high expression levels of both M1-and M2-like protein markers in this study.…”
Section: Fig 7 (Continued)mentioning
confidence: 87%
“…30 Expression profiling of Arg1+ and Arg1-macrophage subpopulations that infiltrated after TBI revealed that they do not separate into true M1-or M2-like transcriptional profiles, but rather adopt mixed molecular phenotypes, and the ratio of macrophage subsets change over time after TBI. 30 Interestingly, blockade of macrophage infiltration by inhibiting CCR2 either by genetic or pharmacological means improves outcomes after TBI. Compared with wild-type mice, CCR2 knockout mice subjected to CCI have reduced lesion volumes, decreased pro-inflammatory gene expression, decreased macrophage infiltration in the injured cortex and improved cognitive function recovery after TBI.…”
Section: Fig 7 (Continued)mentioning
confidence: 99%
“…[46][47][48] To determine the role of CCR2 in monocyte recruitment, we performed TBI in Ccr2 -/ -mice and analyzed the presence of macrophages in the brain. Immunohistochemistry for F4/80 antigen, a marker on both macrophages and microglia, was performed at day 4, a time point where we observed peak macrophage infiltration in this model.…”
Section: The Early Recruitment Of Brain Wound Macrophages Post-tbi Ismentioning
confidence: 99%
“…They, like in other works, see robust Arg1 upregulation early after injury, with distinct Arg1 positive and negative populations (Hsieh et al, 2013). However, after sorting cells based on YFP and analyzing their transcription profiles they found that…”
Section: The Importance Of Macrophage Skew In Cns Injurysupporting
confidence: 64%
“…Arg1 positive cells, which should be M2, do not express many other M2 markers and actually express some M1 markers (Hsieh et al, 2013). These findings are not necessarily surprising, Figure 2.3: Beneficial and detrimental roles for macrophages and neutrophils in CNS injury.…”
Section: The Importance Of Macrophage Skew In Cns Injurymentioning
confidence: 97%